Hubungan Asupan Serat dan Vitamin E dengan Kadar Kolesterol Total pada Penderita Penyakit Jantung Koroner Rawat Jalan di RSUD Dr. Moewardi - Nurani, Agga Thesda (2016)
Coronary heart disease belongs to the group of cardiovascular diseases which are the leading causes of death in Indonesia. High cholesterol level is a risk factor for coronary heart disease. Intakes of fiber and vitamin E that suit our needs can help lowering cholesterol level. This study aimed to determine the correlations between fiber and vitamin E intakes with total cholesterol levels in coronary heart disease outpatients at Dr. Moewardi hospital. The research was an observational study with cross-sectional design. The subjects were 30 coronary heart disease patients aged 30-65 years. Sampling technique used consecutive sampling. Data on fiber and vitamin E intakes were obtained through Semi Quantitative Food Frequency Quesionnare (SQFFQ) method. Data on total cholesterol level were obtained from medical record at Dr. Moewardi hospital. The statistic test used Pearson Product Moment tests. Most respondents had low fiber intake (83,3%). All respondents had low vitamin E intake (100%). The number of respondents who had normal cholesterol levels was 66,7%. The number of respondents who had low fiber intake and had normal cholesterol levels was 68%. The number of respondents who had low intake of vitamin E and had normal cholesterol levels was 66,7%. Statistical analysis showed that there was no correlation between fiber intake and total cholesterol levels with p=0,655. Also, there was no correlation between intake of vitamin E and total cholesterol levels with p=0,615. There was no association between fiber and vitamin E intakes and level of cholesterol in coronary heart disease outpatients at Dr. Moewardi hospital.